Impact of flow hydrodynamics and pipe material properties on biofilm development within drinking water systems. Issue 28 (18th December 2020) - Cowle, Matthew W.; Webster, Gordon; Babatunde, Akintunde O.; Bockelmann-Evans, Bettina N.; Weightman, Andrew J.
ABSTRACT: The aim of this study was to investigate the combined impact of flow hydrodynamics and pipe material on biofilm development in drinking water distribution systems (DWDS). Biofilms were formed on four commonly used pipe materials (namely polyvinyl chloride, polypropylene, structured wall high-density polyethylene and solid wall high-density polyethylene) within a series of purpose built flow cell reactors at two different flow regimes. Results indicate that varying amounts of microbial material with different morphologies were present depending on the pipe material and conditioning. The amount of microbial biomass was typically greater for the biofilms conditioned at lower flows. Whereas, biofilm development was inhibited at higher flows indicating shear forces imposed by flow conditions were above the critical levels for biofilm attachment. Alphaproteobacteria was the predominant bacterial group within the biofilms incubated at low flow and represented 48% of evaluated phylotypes; whilst at higher flows, Betaproteobacteria (45%) and Gammaproteobacteria (33%) were the dominant groups. The opportunistic pathogens, Sphingomonas and Pseudomonas were found to be particularly abundant in biofilms incubated at lower flows, and only found within biofilms incubated at higher flows on the rougher materials assessed. This suggests that these bacteria have limited ability to propagate within biofilms under high shear conditions without sufficient protection (roughness). These findings expand on knowledge relating to the impact of surface roughness and flow hydrodynamics on biofilm development within DWDS. GRAPHICAL ABSTRACT: UF0001